Pembuatan Karbon Aktif Bambu dengan Metode Termolisis dan Karakterisasinya - Stefan Sindim; Heindrich Taunaumang; Alfrie Musa Rampengan (Jurnal FisTa : Fisika dan Terapannya, 2023)
This study aims to determine the manufacture of bamboo activated carbon by the thermolysis method and to know how to characterize bamboo activated carbon after being activated by the thermolysis method and using an activating agent. The method used in this research is the experimental method. Bamboo is carbonized at 350°-400°C and immersed in a 20% phosphoric acid solution. Activated carbon was characterized by Fourier Transform InfraRed spectroscopy (FTIR), X-Ray Diffraction (XRD), and Scanning Electron Microsope-Energy Dispersive X-ray spectrometric (SEM-EDX). Characterization with XRD showed that the 2θ angle of the bamboo carbon after activation was 24°, 37.5°, and 44°. Characterization with FTIR showed that the functional groups detected on activated carbon were O-H, C-H alkane groups, C=O, C=C, C-C , and C-O. Characterization by SEM showed that the activated carbon from the shoots had a neat looking surface. EDX analysis showed that the elemental content of carbon electrodes colored by carbon elements was 78.38%.